Systematic Review of Nurse Performance Appraisal Instruments: Validity, Reliability, and Implications for Nursing Practice - Deltario Novian Joko Sucipto; Purwaningsih Purwaningsih; Nuzul Qur’aniati (Jurnal Ners, 2026)
Accurate assessment of nurse performance is essential to improving healthcare quality, patient outcomes, and organizational effectiveness. Despite the development of various performance appraisal instruments, concerns persist regarding their validity, reliability, fairness, and alignment with clinical practice. This systematic review, conducted following PRISMA guidelines, analyzed studies published between 2020 and 2025 from PubMed, Scopus, ProQuest, and Sage Journals that discussed the development, evaluation, or implementation of nurse performance appraisal tools. From 226 identified articles, 13 met the inclusion criteria. The instruments reviewed ranged from self-assessment and peer/supervisor evaluation to empowerment-based and theoretically grounded models such as self-efficacy and the balanced scorecard. Findings revealed that most instruments positively influenced job satisfaction, empowerment, organizational commitment, and patient outcomes. However, persistent challenges include subjectivity, inconsistent benchmarks, limited validation, and poor communication between appraisers and appraisees. Instruments integrating multiple perspectives and theoretical foundations demonstrated greater comprehensiveness and acceptance. Therefore, future development should prioritize standardization, validity, reliability, fairness, and alignment with organizational goals, positioning performance appraisal as a strategic mechanism to enhance nursing performance and healthcare quality rather than merely an administrative requirement.